2000
DOI: 10.1046/j.1523-1739.2000.99386.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Habitat Mapping into Practical Koala Conservation on Private Lands

Abstract: Identifying and conserving faunal habitat on private lands has been conducted largely on a site‐by‐site basis as development proposals arise. We sought to map koala habitat at a scale suitable for use by a local planning authority so that habitat remnants could be protected and managed while remaining in private ownership. At this scale, the level of detail and accuracy needed by local planners required a new approach to mapping koala habitat. Two independent techniques, community and field surveys, were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 5 publications
0
66
0
Order By: Relevance
“…Identification and mapping the distribution of preferred food trees and tree associations has been a common approach to mapping koala habitat for implementation of regional koala conservation management plans (Lunney et al 2000). In this study, koala scats were found more often than expected (on the basis of tree species abundance) beneath tallowwood and grey gum.…”
Section: Food Tree Preferencesmentioning
confidence: 75%
“…Identification and mapping the distribution of preferred food trees and tree associations has been a common approach to mapping koala habitat for implementation of regional koala conservation management plans (Lunney et al 2000). In this study, koala scats were found more often than expected (on the basis of tree species abundance) beneath tallowwood and grey gum.…”
Section: Food Tree Preferencesmentioning
confidence: 75%
“…Hasegawa 1995;Munks et al 1996;Pahl 1996;Lunney et al 2000;Phillips et al 2000). Barnes (1996) noted that for elephants, direct count methods have been validated and fine-tuned, whereas dung counts are still evolving.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that strong biases could be introduced when landscapes with surface water present (or probably even very moist substrates) are being surveyed. Koalas actually tend to favor wet habitats [21] and so for this species, there is the paradoxical likelihood that there will be a low density of detectable scats present in areas supporting a relatively high density of koalas. Despite this, few studies have attempted to control for decay bias in koala scat surveys and even these studies have tried to account for scat decay by excluding scats older than a certain threshold [20,22,64].…”
Section: Scat Decay Rate and Biasmentioning
confidence: 99%
“…and are difficult to survey directly because of their cryptic, nocturnal habits and their low population density. Scat surveys have thus been widely used in studies of koala distribution [18,19], habitat use [20,21], and abundance [22], as well as frequently forming the basis for management [23]. One source of inaccuracy reported in other species is variability of scat decay linked with diet variability [24]; this should be negligible for koalas which are folivores with a relatively homogeneous diet all year round, relying mainly on a few genera in the Family Myrtaceae, predominantly Eucalyptus, Corymbia, Melaleuca and Lophostemon [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation